2015
DOI: 10.1111/apha.12519
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular endothelin-1 hyper-reactivity is associated with transient receptor potential canonical channels 1 and 6 activation and delayed cerebral hypoperfusion after forebrain ischaemia in rats

Abstract: Our data demonstrates that endothelin-1-mediated influx of extracellular Ca(2+) activates transient receptor potential canonical channels 1 and 6 in cerebral vascular smooth muscle cells. This seems to have an important role in the enhanced cerebral vasoconstriction in the delayed post-ischaemic hypoperfusion phase after experimental forebrain ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…These cardioprotective effects may be due to improved blood flow to ischemic tissue during hypoxia since GsMTx4 causes vascular smooth muscle relaxation by both decreasing mechanically activated excitatory cation currents [110, 111] and down regulation of endothelin-1 stimulated increase in arterial resistance [112, 113]. It may also affect fibroblast conductive properties which are known to play a role in generation of arrhythmias following ischemia [114, 115].…”
Section: Therapeutic Potential Of Gsmtx4mentioning
confidence: 99%
“…These cardioprotective effects may be due to improved blood flow to ischemic tissue during hypoxia since GsMTx4 causes vascular smooth muscle relaxation by both decreasing mechanically activated excitatory cation currents [110, 111] and down regulation of endothelin-1 stimulated increase in arterial resistance [112, 113]. It may also affect fibroblast conductive properties which are known to play a role in generation of arrhythmias following ischemia [114, 115].…”
Section: Therapeutic Potential Of Gsmtx4mentioning
confidence: 99%
“…Based on their amino acid sequences and functional similarities, the TRPC family can be divided into 4 groups: TRPC1, TRPC2, TRPC4/5, and TRPC3/6/7. Studies have demonstrated that TRPC6 channel has a critical role in promoting neuronal survival against cerebral ischemic injury 1315 . Sossin et al .…”
Section: Introductionmentioning
confidence: 99%
“…The increased expression of ET B and 5‐HT 1B receptors in the VSMCs of the cerebral pial arteries resulted in an increased vascular contractility correlating with cerebral hypoperfusion of the forebrain (Johansson et al . , ). Furthermore, plasma, cerebrospinal fluid and brain parenchyma concentrations of endothelin‐1 (ET‐1) and brain parenchyma concentrations of 5‐hydroxytryptamine (5‐HT) were previously found to increase after cerebral ischaemia (Zervas et al .…”
mentioning
confidence: 99%